Determining effects of an all weather logging road on winter woodland caribou habitat use in south-eastern Manitoba - Schindler, Doug W.; Walker, David; Davis, Tim; Westwood, Richard (Rangifer, 2007)
The Owl Lake boreal woodland caribou population is the most southerly population in Manitoba. It is provincially ranked as a High Conservation Concern Population. Forestry operations exist in the area and there are plans for further forest harvest and renewal. The Happy Lake logging road is the only main access through the Owl Lake winter range. This logging road is currently closed to the public and access is limited to forestry operations during specific times of the year. An integrated forestry/caribou management strategy for the area provides for the maintenance of minimum areas of functional habitat. Habitat quality along the road was compared to habitat quality in the winter core use areas, within the winter range and outside the winter range. To evaluate the extent of functional habitat near the road, we conducted animal location and movement analysis using GPS data collected from January 2002 to March 2006. Habitat quality in the winter range, core use areas and along the road were assessed and found to be similar. Analysis of caribou locations and movement illustrate less use of high quality habitat adjacent to the Happy Lake Road. Loss of functional habitat is suggested to occur within 1 kilometre of the road. This potential loss of functional habitat should be incorporated into integrated forestry and caribou conservation strategies. Road management is recommended to minimize the potential sensory disturbance and associated impacts of all weather access on boreal woodland caribou.